The Effect of Capital Adequacy, Financing, and Economic Growth on The Profitability of Islamic Commercial Banks In The Period 2019-2024 - Tamami, Tamami; Muhsin, Moh.; Fatoni, Ahmad (JURNAL EKONOMI SYARIAH, 2025)
Introduction to The Problem: This study was conducted due to the gap in the theory of the financial ratios CAR, NPF, MSME Financing, non-MSMEs, and economic growth towards Return on Assets (ROA) at Islamic Commercial Banks in Indonesia. On the other hand, the development of bank ROA in the era of globalization and technology stagnation at 2% is lagging when compared to conventional banks with higher profitability. Whereas the majority are Muslim which can drive profits from users of Islamic Commercial Bank services. So this study needs to analyze each relationship between variables and the profitability of Islamic banks.Purpose/Objective Study: To see whether CAR, NPF, MSME Financing, Non-MSME Financing, and economic growth affect profitability partially and simultaneously.Design/Methodology/Approach: This study uses a quantitative approach through time series regression analysis and error correction model (ECM) testing using the Eviews 12.0 computer program.Findings: In the long run, MSME financing and economic growth have a positive effect on ROA. While in the short run, CAR, NPF, MSME financing and economic growth have a positive impact on ROA.Paper Type: Research Article